dgdgdf - t , a N = q k a k 2-a 2 T = p ( e 2 t + e-2 t )-(...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
MATH 241H - EXAM 1 - February 12, 2007 1. Using P 0 = (1 , - 1 , 4) and L = (2 , 3 , 0), we get x - 1 2 = y + 1 3 , z = 4 2. Using P 0 = (2 , 1 , - 1) and N = (1 , - 3 , 2), we get ( x - 2) - 3( y - 1) + 2( z + 1) = 0. 3. lim t 1 F ( t ) = i + k since this is the limit from either direction. 4. v ( t ) = sin(2 t ) / 2 i + (1 - cos(2 t )) / 2 j + ( t + 1) k r ( t ) = (5 - cos(2 t )) / 4 i + (1 + t/ 2 - sin(2 t ) / 4) j + ( t 2 / 2 + t ) k 5. v ( t ) = e t i - e - t j + ( 2) k k v ( t ) k = e 2 t + e - 2 t + 2 = e t + e - t a ( t ) = e t i + e - t j , v ( t ) × a ( t ) = - 2 e - t i + 2 e t j + 2 k , so L = Z 1 0 ( e t + e - t ) dt = e - e - 1 a T = e t - e -
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: t , a N = q k a k 2-a 2 T = p ( e 2 t + e-2 t )-( e 2 t + e-2 t-2) = 2 . = 2 e-2 t + 2 e 2 t + 4 ( e t + e-t ) 3 = 2 ( e t + e-t ) 2 . 6. (a) T (b) F (should be a b = k a k k b k cos .) (c) F (should be k c a k = | c |k a k ) (d) T...
View Full Document

This note was uploaded on 04/04/2010 for the course MATH 113 taught by Professor Staff during the Spring '08 term at Maryland.

Ask a homework question - tutors are online